ANALISIS PENGGUNAAN SMARTPHONE SEBAGAI MEDIA PEMBELAJARAN TERHADAP HASIL BELAJAR SISWA SMAN 1 TELUK KERAMAT - Ruziana, Ruziana; Imran, Imran; Salim, Izhar (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis study aims to determine whether or at least the influence of smartphone use on learning outcomes. The variables of this research are independent variable (X) smartphone usage and dependent variable (Y) learning result. The research method used is kuntitatif method by using inferential statistics of influence study. Techniques used in data collection in the form of indirect communication techniques and documentary study techniques, with data collection tools in the form of questionnaires along with note sheets obtained from students or samples totaling 56 oarang. The result of hypothesis testing proves that there is influence but not significance between smartphone usage to learning result with r count 0,155 <t table 2,005. While the value of regression equation is Y = 74,496 + 0,020 X, indicating that smartphone usage increase 1, hence learning result increase 0,020. The determinant value is adjusted R ^ = 0,020 which means contribution of smartphone usage effect to learning result equal to 1,8% which is in very low category and 98,2% determined by other factor which not discussed in research. Keywords: Analysis, Smartphone Usage, Student Sociology Learning Results